2020
DOI: 10.1007/s00227-020-03739-1
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the neighbourhood: assessing the impact of kelp harvest on foraging behaviour of the European shag

Abstract: Coastal kelp forest ecosystems create dynamic and productive habitats, supporting a wide range of epiphytic flora, invertebrates, fish and seabirds. Worldwide, kelp is harvested commercially, affecting kelp-associated animal communities. There is, however, limited knowledge of how fish and seabird respond to kelp harvest, highlighting the need to evaluate the ecological impact of harvest on all ecosystem levels. Using 6 years of GPS-tracking data, we examined the effects of kelp harvest on foraging behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…While it was suggested that Phalacrocorax carbo foraging behaviour was altered due to harvesting, its population development was unchanged [ 128 ], suggesting no long-term effects. No alterations in the diving activity of Phalacrocorax aristotelis due to kelp harvesting were observed [ 129 ]. As birds such as P. carbo and P. aristotelis do not form obligate relationships with seaweed, the effects of harvesting on such species may be limited or absent.…”
Section: Resources Sustainability and Regulation Of Seaweed-based Bio...mentioning
confidence: 99%
“…While it was suggested that Phalacrocorax carbo foraging behaviour was altered due to harvesting, its population development was unchanged [ 128 ], suggesting no long-term effects. No alterations in the diving activity of Phalacrocorax aristotelis due to kelp harvesting were observed [ 129 ]. As birds such as P. carbo and P. aristotelis do not form obligate relationships with seaweed, the effects of harvesting on such species may be limited or absent.…”
Section: Resources Sustainability and Regulation Of Seaweed-based Bio...mentioning
confidence: 99%
“…Seabirds are among the most threatened taxonomic groups of birds, facing a multitude of mostly anthropogenic stressors (Dias et al, 2019). These range from oil exploration (Votier et al, 2005;Votier et al, 2008), establishment of wind farms (Garthe and Hüppop, 2004;Furness et al, 2013;Peschko et al, 2020), kelp harvesting (Lorentsen et al, 2010;Christensen-Dalsgaard et al, 2020), bycatch (Anderson et al, 2011;Z ̌ydelis et al, 2013), ship traffic (Dehnhard et al, 2020a) and fisheries (Cury et al, 2011;Saraux et al, 2020) to various impacts of climate change (e.g. Greḿillet and Boulinier, 2009;Keogan et al, 2018), but also include predation by introduced predators (Craik, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Shags are vulnerable to disturbance by boats (Velando and Munilla, 2011), and incidental mortality in gillnet fisheries (Z ̌ydelis et al, 2013;Christensen-Dalsgaard et al, 2019). Furthermore, kelp harvesting in areas used by shags for foraging has the potential to affect foraging success (Christensen-Dalsgaard et al, 2020). Finally, aquaculture installations can easily lead to a reduction in available coastal marine habitat, increased boat traffic and therefore higher disturbance effects, and shags are perceived as a pest by the aquaculture industry (Beveridge, 2001).…”
Section: Introductionmentioning
confidence: 99%